Thermofluid patterns at a curved liquid drop surface - Gopalkrishnan, Deeban (2019)
The evaporation dynamics surrounding numerous biomedical, technological and industrial scale applications include mass and heat transfer as their main working principles. Plenty of background study and researches have been conducted to relate key physical conditions with thermal patterns forming on surfaces. The infrared camera has long been able to ascertain the thermal pattern formations and remains as an essential tool during the conduction of experiments. It was primarily chosen to aid in visually viewing complex patterns occurring within the droplet when it was subjected to various conditions. With the working fluid chosen to be pure ethanol, it would then be tested in an evaporation chamber, having employed transient and steady-state evaporation as the 2 interests of this study. During the transient state evaporation process, the working fluid was set to pump out a fixed volume of 0.02ml at a fixed flow rate of 0.6ml/min. Together with infrared and side view images, the behaviour of the droplet in terms of hydrothermal waves, contact angle, diameter and volume were then explored as temperature and vacuum pressure varied. As for steady-state evaporation, the height and hence the volume of the droplet was pre-determined and kept constant throughout the study. The infrared and side-view images were then analysed for hydrothermal waves and contact angles respectively. While this study targeted on the analysis of a pure volatile liquid, future study can be undertaken to introduce a scope on different concentrations of the working liquid where thermal conductivity varies widely, in turn affecting the temperature gradient and thermal patterns of the fluid.